The origin of lithogenic sediment in the south-western Ross Sea and implications for iron fertilization. Issue 4 (26th February 2016) - Winton, V.H.L.; Dunbar, G.B.; Atkins, C.B.; Bertler, N.A.N.; Delmonte, B.; Andersson, P.S.; Bowie, A.; Edwards, R.
Abstract: Summer iron (Fe) fertilization in the Ross Sea has previously been observed in association with diatom productivity, lithogenic particles and excess Fe in the water column. This productivity event occurred during an early breakout of sea ice via katabatic winds, suggesting that aeolian dust could be an important source of lithogenic Fe required for diatom growth in the Ross Sea. Here we investigate the provenance of size-selected dust deposited on sea ice in McMurdo Sound, south-western (SW) Ross Sea. The isotopic signature of McMurdo Sound dust (0.70533< 87 Sr/ 86 Sr<0.70915 and -1.1<εNd (0)<3.45) confirms that dust is locally sourced from the McMurdo Sound debris bands and comprises a two-component mixture of McMurdo Volcanic Group and southern Victoria Land lithologies. In addition, the provenance of lithogenic sediment trapped in the water column was investigated, and the isotopic signature (εNd (0)=3.9, 87 Sr/ 86 Sr=0.70434) is differentiated from long-range transported dust originating from South America and Australia. Elevated lithogenic accumulation rates in deeper sediment traps in the Ross Sea suggest that sinking particles in the water column cannot simply result from dust input at the surface. This discrepancy can be best explained by significant upwelling and remobilization of lithogenic Fe from the sea floor.